Whatsapp : um estudo sobre a cultura digital e as possibilidades de seu uso na prática pedagógica - Silva, Viviane Salarolli de Souza (2018)
This study is the result of the research developed in the Master's Degree in Education, in the line of research: School Cultures and Languages with the following objectives: 1) To scrutinize the possibility of using the application - WhatsApp - in the pedagogical practice of the researched teachers. In what way (how) and in what moment (when) does this happen; 2) Describe the favorable and unfavorable experiences in the use of the device inside and outside the spaces through the reports of the postgraduate students in the Education Institute of the Federal University of Mato Grosso (PPGE / IE / UFMT) school children; 3) Analyze how communication between teachers and students is established and whether these teachers consider themselves prepared to work with digital culture practitioners, members of the cybergeneering according to the metaphor of the French philosopher and sociologist Pierre Lévy; 4) To verify the teachers' understanding of the relation between teaching and technology, to what extent this conception helps them in their teaching practice. The study is based on authors such as Zygmunt Bauman (2007); Pierre Lévy (2010); Gilles Lipovetsky (2005, 2007); Jean-François Lyotard (2004); Wim Veen & Bem Vrakking (2009); Marshall McLuhan (2007), among others. For the education we talk with Selma Garrido Pimenta; Evandro Ghedin through the work Reflexive Professor in Brazil (2005); José Manuel Moran (2012) and Silas Borges Monteiro (2013). The methodology used is based on the qualitative approach, being a research of a descriptive nature, based on some tools that this approach uses, such as systematic observation and participant, questionnaire, online interviews, composition of reports and a closer look on the part of the researcher to the observed data without interference in the researched scenario: virtual environment, a group in the application - WhatsApp -, titled 'the feds'. The group is comprised of a sample of fifteen students from the Master's Course in Education (PPGE / IE / UFMT), Cuiabá-MT campus, concomitantly, teachers who work in different teaching segments. In addition to the increasing use of digital technologies, interaction between users and interactivity with different devices, a new relationship with knowledge and new pedagogical practices is necessary (LÉVY, 2010). The study intends to investigate the possibilities of using the application, in the aid of pedagogical practice, mediating the communication between teachers and students. The data were collected through a questionnaire composed of two parts: characterization of the teachers and the possibilities of using the application in the school environment. The results reveal that, in addition to the possibilities and ways of using the device, through the reports of the teachers participating in the research, it is noticed that the free mobile message service application is being used by teachers and students in the perspective of one more device that contributes to the teaching and learning process of the school content.